Risk Factors Associated with Dengue Transmission and Spatial Distribution of High Seroprevalence in Schoolchildren from the Urban Area of Medellin, Colombia - Leidy Diana Piedrahita; Ivony Y. Agudelo Salas; Katherine Marin; Andrea I. Trujillo; Jorge E. Osorio; Sair Orieta Arboleda-Sanchez; Berta Nelly Restrepo (Canadian Journal of Infectious Diseases and Medical Microbiology)
Dengue fever is an increasing health problem in tropical and subtropical regions. During 2010 in Medellin, the younger population presented a particularly high dengue incidence rate. This study estimated dengue virus (DENV) transmission in schoolchildren (aged 5–19 years) in Medellin from 2010 to 2012. A longitudinal serological survey (IgG) and spatial analysis were conducted to determine the distribution of DENV seroprevalence. A total of 4,385 schoolchildren participated for at least one year. Dengue seroprevalence significantly increased during the studied period (53.8% to 64.6%; p<0.001). A significantly higher seroconversion rate was observed in 2010-2011 (16.8%) compared to 2011-2012 (7.8%). Multivariate regression analysis showed that the main factor associated with the seroprevalence was the aging. Furthermore, in 2010, patients with high socioeconomic status presented a lower risk. Predominant multitypic and DENV4 monotypic antibody responses were demonstrated. Geostatistical analysis evidenced a temporal clustering distribution of DENV seroprevalence in 2010. Population density and Ae. aegypti House Index were significantly correlated with the observed pattern. This study revealed high DENV transmission in schoolchildren determined as “sentinel population.” High DENV risk was found in districts with combined poorly socioeconomic conditions and densest human and mosquito populations. These findings may allow to target population for effective prevention and vaccination campaigns.